ANALISIS NILAI BUDAYA DALAM NOVEL TENGGELAMNYA KAPAL VAN DER WIJCK KARYA HAMKA - Alamsyah, Nur; Hayati, Nur; Yunus, Syarifudin (Cahaya Ilmu Bangsa Institute, 2025)
This study aims to reveal and analyze the cultural values contained in the novel Tenggelamnya Kapal Van der Wijck by Hamka. This research employs a qualitative approach with a descriptive-analytical method to examine the representation of Minangkabau culture in the story. The results of the study conclude that the novel is rich in cultural values, especially those of Minangkabau, and highlights the conflict between traditional and modern values. The Minangkabau society is depicted as deeply rooted in customs, including a matrilineal kinship system and a strong family role in matchmaking. Cultural values influence social values, as reflected in the strong social hierarchy between the aristocracy (